Alteration of brain connectivity in neurologically asymptomatic patients with chronic kidney disease. Issue 16 (23rd April 2021) - Lee, Yoo Jin; Yoon, Eunjae; Park, Sihyung; Kim, Yang Wook; Kim, Si Eun; Ko, Junghae; Park, Jin Han; Park, Kang Min; Kim, Il Hwan; Park, Bong Soo
Abstract : Abstract: Our previous study demonstrated that patients with end-stage renal disease had decreased structural and functional brain connectivity, and there was a significant association between brain connectivity and cognitive function. The aim of this study was to evaluate the alterations of structural and functional connectivity using graph theoretical analysis in neurologically asymptomatic patients with relatively early-stage chronic kidney disease (CKD). We enrolled 18 neurologically asymptomatic patients with early CKD and 28 healthy controls. All the subjects underwent diffusion-tension imaging and resting functional magnetic resonance imaging. We calculated structural and functional connectivity based on diffusion-tension imaging and resting functional magnetic resonance imaging using a graph theoretical analysis. Then, we investigated differences of structural and functional connectivity between the CKD patients and the healthy controls. All the measures of structural connectivity were significantly different between the patients with CKD and healthy controls. The global efficiency, local efficiency, mean clustering coefficient, and small-worldness index were decreased, whereas the characteristic path length was increased in the patients with CKD compared with healthy controls. The structural betweenness centrality of the left calcarine and right posterior cingulum was also significantly different from that in healthy participants. However, all the measures of global functional connectivity in patients with CKD were not different from those in healthy controls. In patients with CKD, the functional betweenness centrality of the right insular cortex, right occipital pole, and right thalamus was significantly different from that in healthy participants. There are significant alterations of the global structural connectivity between the patients with CKD and the healthy subjects, whereas the global functional connectivity of the brain network is preserved. We find that the efficiency of the structural brain network is decreased in the patients with CKD. Abstract : Supplemental Digital Content is available in the text